(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2021)
This article addresses the formation practices that students from the Trabajo Social Faculty (UNLP) carried through at El Bichicuí. This memory site was an operational house for the armed political organization Montoneros. The analysis is focused on the practices and social representations that arise amongst teachers, students, and managers of the site. From these experiences stem diverse intersubjective memory-building practices. An ethnographic methodological approach is implemented, through observations with different degrees of participation and in-depth interviews. Regarding the teacher’s practices, some of the questions involved try to explain the motives behind the choice of El Bichicuí as a location for the formation of students from Trabajo Social, which activities and ways of intervention they perform at the place and the role of the teachers.